Role of Bacillus licheniformis VS16-Derived Biosurfactant in Mediating Immune Responses in Carp Rohu and its Application to the Food Industry - Giri, Sib Sankar; Sen, Shib Sankar; Jun, Jin Woo; Sukumaran, V.; Park, Se Chang (Frontiers in Microbiology, 2017)
Multifarious applications of Bacillus licheniformis VS16-derived biosurfactant were explored. Labeo rohita fingerlings were injected intraperitoneally with 0.1 mL of phosphate-buffered saline (PBS) containing purified biosurfactant at 0 (control), 55 (S55), 110 (S110), 220 (S220), or 330 (S330) μg mL-1 concentrations. Various immunological parameters and the expression of immune-related genes were measured at 7, 14, and 21 days post-administration (dpa). At 21 dpa, fish were challenged with Aeromonas hydrophila and mortality was recorded for 14 days. Immune parameters such as lysozyme levels (39.29 ± 2.14 U mL-1), alternative complement pathway (61.21 ± 2.38 U mL-1), and phagocytic activities (33.37 ± 1.2%) were maximum (P < 0.05) in the S220 group at 14 dpa; but immunoglobulin levels (11.07 ± 0.83 mg mL-1) were highest in the S220 group at 7 dpa, compared to that in controls. Activities of digestive enzymes (amylase, protease, and lipase) were higher (P < 0.05) in the S220 and S330 groups than in the control group. Regarding cytokine gene expression, pro-inflammatory cytokines (TNF-α and IL-1β) were down-regulated (P < 0.05) in the S220 and S330 groups. Expression of IL-10, TGF-β, and IKB-α were up-regulated in the S220 and S330 groups at 14 dpa, with the highest levels in the S220 group. The expression of NF-κB p65 and IKK-β were down-regulated in treatment groups, and were lowest (P < 0.05) in the S220 group. The highest post-challenge survival rate (72.7%) was recorded in S220 group. Further, the potential of this substance to inhibit biofilm formation, and heavy metal removal from vegetables were also evaluated. Biosurfactant was effective in inhibiting biofilm formation up to 54.71 ± 1.27%. Moreover, it efficiently removed cadmium (Cd) from tested vegetables such as carrot, radish, ginger, and potato, with the highest removal efficiency (60.98 ± 1.29%) recorded in ginger contaminated with Cd. Collectively, these results suggest that isolated biosurfactant could be used in the aquaculture industry, in addition to its potential application to the food industry.